The influence of foliar application of selenium (VI) on the concentration of Fe, Mn, Cd, Cu, Zn, S, and Mo in common buckwheat - Vogrinčič, Maja (Fagopyrum (Ljubljana), 2025)
Selenium in the form of selenate (Se VI) was foliarly applied to buckwheat plants to evaluate its influence on the up-take and accumulation of other selected elements, including copper (Cu), zinc (Zn), sulfur (S), molybdenum (Mo), iron (Fe), manganese (Mn), and cadmium (Cd). Among these, Cu, Zn, Mo, Fe, and Mn are essential elements while cadmium, on the other hand, is a toxic pollutant absorbed by plants from contaminated soils. Foliar selenium (VI) application resulted in modest changes in the concentrations of Cd, Mo, Fe, Mn, and S in the leaves; Cu in the husks; and Mo and Mn in inflorescences. However, selenium had no significant effect on Zn accumulation. These results suggest that foliar application of selenium (VI) may both enhance and inhibit the uptake of specific elements, with effects varying by plant tissue.
Keywords: common buckwheat; elementi v sledovih; navadna ajda; selen; selenium; Tartary buckwheat; tatarska ajda; trace elements